PEMBIAYAAN INOVATIF DALAM PENINGKATAN AKSES PELAYANAN KESEHATAN MASYARAKAT: STUDI LITERATUR - Yasmine Anta Syahri; Indah Rahayu Ritonga, Suhayla Azhari Silalahi, Fitriani Pramita Gurning (CV. Adiba Aisha Amira, 2024)
The increase in population is caused by increasing birth rates and life expectancy due to advances in health technology. This type of research involves synthesizing, summarizing, and reviewing a number of previous studies to create a systematic review of the body of knowledge that has been published in online scientific journals. Literature on financing innovation for health services in Indonesia is the focus of this research. The research results obtained are that to ensure that the quality of service improves as much as possible, several factors need to be considered: how quickly patients are treated and cared for; how often the patient is examined by a doctor during treatment; the types of services offered at the hospital; number of trained doctors and paramedics; and supplies. medicines and equipment owned by the hospital to help with the treatment or care process. Various developments in financing innovation for health services currently show quite significant and good developments. The access to health services provided is also quite good with adequate facilities so that they can take their health seriously.